2019
DOI: 10.3390/coatings9120813
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Microwave Absorption of Asphalt Mixtures Containing Magnetite Powder

Abstract: This article is intended to investigate the microwave heating performance of asphalt mixtures containing magnetite powders (MPAM). For this purpose, the surface temperatures of asphalt mixtures containing different dosages of magnetite powders were measured during microwave heating. The low-temperature bending test and water sensitivity test were also conducted to evaluate the performance of MPAM. Heating rate and reflection loss of different thicknesses of MPAM were determined using a microwave heating test a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…As can be seen from Figure 11 , the surface temperature of the asphalt mixture mixed with CFe is significantly higher than that of the control group, and the temperature increases with the replacement rate of CFe. This heating efficiency is similar to the results obtained by Guan et al [ 38 ], who added magnetite powder as a microwave-absorbing material to asphalt concrete and found that the microwave heating rate of the asphalt mixture with magnetite powder was significantly higher than that of traditional asphalt mixture.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As can be seen from Figure 11 , the surface temperature of the asphalt mixture mixed with CFe is significantly higher than that of the control group, and the temperature increases with the replacement rate of CFe. This heating efficiency is similar to the results obtained by Guan et al [ 38 ], who added magnetite powder as a microwave-absorbing material to asphalt concrete and found that the microwave heating rate of the asphalt mixture with magnetite powder was significantly higher than that of traditional asphalt mixture.…”
Section: Resultssupporting
confidence: 90%
“…Ding et al [ 12 ] found that a 1% mass ratio of Al 3 O 4 and Fe 3 O 4 mixed 1:1 at 2.45 GHz had a better deicing efficiency. Guan et al [ 38 ] studied the microwave heating performance of adding magnetite powder to an asphalt mixture and found that increasing the dosage of magnetite powder increased the heating rate and the low-temperature performance. The recommended dosage of magnetite powder was 60%.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the addition of CGP contributes to the improvement of the microwave heating ability. This may be because the compounds composed of Si and Fe, Al and other related metals have good electromagnetic properties [44,45]. And the comprehensive content of silicon oxide, iron oxide and alumina in CGP is significantly higher than that in CMP (Table 5), which helps to enhance the absorption capacity of microwaves [35,36].…”
Section: Microwave Heating Ability Of Asphalt Mixes With Different Fi...mentioning
confidence: 99%
“…Some studies have shown that Si is an electric loss microwave absorbing material [32], and ferrite can absorb microwaves by means of both dielectric loss and magnetic loss, mainly through magnetic loss [33]. The compounds composed of Si and related metals such as Fe and Al have good electromagnetic properties and can absorb microwaves [44,45]. Compared with CMP, CGP may have better microwave absorption efficiency.…”
Section: Chemical Composition Of Fillersmentioning
confidence: 99%
“…Aminul Haque, M. et al demonstrated that the addition of three different fibrous materials can effectively improve the bending properties and compressive strength of the phosphate cement composites [14][15][16]. Several studies have shown that the road performance of asphalt mixture can be enhanced by the addition of fibers [17][18][19][20]. However, different types of fibers have different performance improvements on asphalt mixtures.…”
Section: Introductionmentioning
confidence: 99%